Is natural (6S)-5-methyltetrahydrofolic acid as effective as synthetic folic acid in increasing serum and red blood cell folate concentrations during pregnancy? A proof-of-concept pilot study - Kelsey M. Cochrane; Chantal Mayer; Angela M. Devlin; Rajavel Elango; Jennifer A. Hutcheon; Crystal D. Karakochuk (Trials, 2020)
Abstract Background North American health authorities recommend 0.4 mg/day folic acid before conception and throughout pregnancy to reduce the risk of neural tube defects. Folic acid is a synthetic form of folate that must be reduced by dihydrofolate reductase and then further metabolized. Recent evidence suggests that the maximal capacity for this process is limited and unmetabolized folic acid has been detected in the circulation. The biological effects of unmetabolized folic acid are unknown. A natural form of folate, (6S)-5-methyltetrahydrofolic acid (Metafolin®), may be a superior alternative because it does not need to be reduced in the small intestine. Metafolin® is currently used in some prenatal multivitamins; however, it has yet to be evaluated during pregnancy. Methods/design This double-blind, randomized trial will recruit 60 pregnant women aged 19–42 years. The women will receive either 0.6 mg/day folic acid or an equimolar dose (0.625 mg/day) of (6S)-5-methyltetrahydrofolic acid for 16 weeks. The trial will be initiated at 8–21 weeks’ gestation (after neural tube closure) to reduce the risk of harm should (6S)-5-methyltetrahydrofolic acid prove less effective. All women will also receive a prenatal multivitamin (not containing folate) to ensure adequacy of other nutrients. Baseline and endline blood samples will be collected to assess primary outcome measures, including serum folate, red blood cell folate and unmetabolized folic acid. The extent to which the change in primary outcomes from baseline to endline differs between treatment groups, controlling for baseline level, will be estimated using linear regression. Participants will have the option to continue supplementing until 1 week postpartum to provide a breastmilk and blood sample. Exploratory analyses will be completed to evaluate breastmilk and postpartum blood folate concentrations. Discussion This proof-of-concept trial is needed to obtain estimates of the effect of (6S)-5-methyltetrahydrofolic acid compared to folic acid on circulating biomarkers of folate status during pregnancy. These estimates will inform the design of a definitive trial which will be powered to assess whether (6S)-5-methyltetrahydrofolic acid is as effective as folic acid in raising blood folate concentrations during pregnancy. Ultimately, these findings will inform folate supplementation policies for pregnant women. Trial registration ClinicalTrials.gov, ID: NCT04022135 . Registered on 14 July 2019.